Green Corrosion Inhibitor of Aluminum in Artificial Acid Rain by Rambutan Peel Extract - Fadel Mohamed BinYehmed (Journal of Pure & Applied Sciences, 2019)
The inhibitive action of methanolic Rambutan Peel Extract (RPE) as green corrosion inhibitor of aluminum was investigated in artificial acid rain (AAR) using potentiodynamic polarization. The results revealed that RPE was an effective eco-friendly inhibitor for aluminum. The results also showed the inhibition efficiency increased with increase extract for Al and it reached maximum IE 93.18% at 8 g/L, and the values of IE decreased with temperature. The inhibitive action is attributed to the adsorption of the inhibitor molecules on the metal surface following Langmuir adsorption isotherm. Standard free energy of adsorption ∆Gads (-12.81 to -15.107 kJ mol-1), a physical adsorption mechanism is proposed for the adsorption of the inhibitor on the surface of aluminum.